Investment Strategies for Increasing the Agribusiness Competitiveness - Dudnik, Alexey V.; Cherdakova, Tatyana A. (Economy of Regions, 2021)
Nowadays, investment in national agri-food systems is of significant interest, as it is a necessary condition for implementing large-scale technological innovations which are crucial not only for this particular system, but for Russian economy in general. The research aims to study how investments affect the competitiveness of the Russian agri-food system and to propose a conceptual framework for strategic agribusiness management at the regional and national levels. We hypothesise that competitiveness indicators, including cost intensity of production, depend on the investment in agribusiness. Due to low access to credit, agricultural companies look for alternative investment strategies, one of which is investment subsidies in commodity production. The hypothesis was tested by examining a sample of organisations engaged in agri-food production. The sample includes profitable companies investing in production development. Sample analysis confirmed the initial hypothesis that investments into technological modernisation of production significantly influence its competitiveness. When developing a strategy for increasing the competitiveness of agri-food systems in terms of investment provision, it is advisable to consider not only quantitative (amount of support), but also structural aspects of support. In particular, we suggest the government to introduce the practice of providing investment subsidies to agricultural commodity producers with participation in the recipients’ capital to support their development. The research results can be used in further studies concerning the management of the agribusiness competitiveness.